Statement of the Financial Economists Roundtable: Corporate Tax Reform. Issue 3 (27th October 2017) - Boot, Arnoud; Logue, Dennis; Spatt, Chester
Abstract : Corporate tax reform has been a controversial issue in the U.S. for several years, particularly as U.S. companies have accumulated cash in lower‐tax overseas subsidiaries, while some have used "inversions" to establish overseas corporate domiciles. Two features of U.S. corporate taxation stand out: 1. U.S. corporate income tax rates are the highest in the industrialized world. The federal rate is 35%; and, when combined with state taxes, it averages 39%, as compared to an OECD average of 24%. 2. U.S. corporations pay U.S. tax on their worldwide income, but can choose to avoid indefinitely corporate tax on foreign profits by not repatriating them. Neither feature is present in most other Western countries, where the norm is a "territorial" system that taxes companies only on their domestic profits. The Trump administration has proposed to cut U.S. corporate tax rates to 20%, thereby bringing them down to the OECD average, and to adopt a territorial tax regime like those found in most other Western nations. In this statement signed by 31 senior financial economists, the authors recommend cutting U.S. corporate tax rates, but retaining the current system of taxing the worldwide profits of U.S. companies (while giving them credit for taxes paid in overseas jurisdictions). Once U.S. rates drop to the international average, the economists point out, U.S. companies would have much less incentive under the worldwide system to use transfer pricing schemes to shift their profits to low‐tax jurisdictions than under the proposed territorial alternative. Indeed, under the current system, if the lower rates under consideration are enacted, the location of a company's business activity (including the firm's underlying intellectual property) would not affect its taxation. Along with lower corporate tax rates, the economists also recommend that Congress limit or remove the corporate option to defer the taxation of offshore profits and provide a schedule for repatriating off‐shore funds, using the inducement of the now lower rates as well as the possibility of a "tax holiday."